Factors Related to Dengue Hemorrhagic Fever (DHF) in Bontang Kuala Sub- district, North Bontang District - Shandy, Adelia Fitria; Badrah, Sitti; Sedionoto, Blego (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2023)
Dengue Hemorrhagic Fever is one of the leading public health problems in Indonesia. The number of DHF pain in Bontang Kuala Sub-district has increased over the past three years, namely 5 cases in 2019, 19 cases in 2020, and 33 cases in 2021. This study aims to determine several factors related to dengue disease in Bontang Kuala Sub-district, North Bontang District. This type of research used a cross-sectional study design. The population in this study was 1,791 households and a sample of 91 respondents. Samples were taken using the proportional random sampling method. The data analysis technique used a chi-square test with a degree of meaningfulness (p = 0.05). The results of this study showed that 68.1% of respondents had poor used goods management with (p = 0.000), 65.9% had good waste disposal facilities with (p = 0.164), 64.8% had a habit of hanging clothes less well with (p = 0.001) and 72.5% had a habit of using anti- mosquito lotion less well with (p = 0.002). This research advises people to make more frequent efforts to eradicate mosquito nests (PSN) coupled with avoiding the habit of hanging clothes and using mosquito-repellent lotions so that the transmission of DHF disease can be reduced.